Adherence of HIV clinics to guidelines for the delivery of TB screening among people living with HIV/AIDS in Ghana - Solomon A. Narh-Bana; Tobias F. Chirwa; Esnat D. Chirwa; Frank Bonsu; Latifat Ibisomi; Mary Kawonga (BMC, 2021)
Abstract Background Tuberculosis screening of people living with HIV (PLHIV) - an intervention to reduce the burden of TB among PLHIV - is being implemented at HIV clinics in Ghana since 2007, but TB screening coverage remains low. Facility adherence to intervention guidelines may be a factor but is missing in implementation science literature. This study assesses the level of HIV clinic adherence to the guidelines and related facility characteristics in selected district hospitals in Ghana. Methods This cross-sectional study was conducted in all 27 district hospitals with HIV clinics, X-ray and geneXpert machines in Ghana. These hospitals are in 27 districts representing about 27% of the 100 district hospitals with HIV clinics in Ghana. A data collection tool with 18-items (maximum score of 29) was developed from the TB/HIV collaborative guidelines to assess facility adherence to four interrelated components of the TB screening programme as stated in the guidelines: intensive TB case-finding among PLHIV (ITCF), Isoniazid preventive therapy initiation (IPT), TB infection control (TIC), and programme review meetings (PRM). Data were collected through record review and interviews with 27 key informants from each hospital. Adherence scores per component were summed to determine an overall adherence score per facility and summarized using medians and converted to proportions. Facility characteristics were assessed and compared across facilities with high (above median) versus low (below median) overall adherence scores, using nonparametric test statistics. Results From the 27 key interviews and facility records reviewed, the median adherence scores for ITCF, IPT, TIC, and PRM components were 85.7% (IQR: 85.5-100.0), 0% (IQR: 0-66.7), 33.3% (IQR: 33.3-50.0), and 90.0% (IQR: 70.0-90.0), respectively. The overall median adherence score was 62.1% (IQR: 58.6-65.1), and 17 clinics (63%) with overall adherence score above the median were categorized as high adherence. Compared to low adherence facilities, high adherence facilities had statistically significant lower PLHIV clinic attendees per month (256 (IQR: 60-904) vs. 900 (IQR: 609-2622); p = 0.042), and lower HIV provider workloads (28.6 (IQR: 8.6-113) vs. 90 (IQR: 66.7-263.5); p = 0.046), and most had screening guidelines (76%, p < 0.01) and questionnaire (80%, p < 0.01) available on-site. Conclusion PRM had highest score while the IPT component had the lowest score. Almost a third of the facilities implemented the TB screening programme activities with a high level of adherence to the guidelines. We suggest to ensure adherence to all four components, reducing staff workloads and making TB screening questionnaires and guidelines available on-site would increase facility adherence to the intervention and ultimately achieve intervention targets.